Negotiating memory from the Romans to the twenty-first century
1 online resource
Keywords: Manipulation of the past and forced erasure of memories have been global phenomena throughout history, spanning a varied repertoire from the destruction or alteration of architecture, sites, and images, to the banning or imposing of old and new practices. The present volume addresses these questions comparatively across time and geography, and combines a material approach to the study of memory with cross-disciplinary empirical explorations of historical and contemporary cases. This approach positions the volume as a reference-point within several fields of humanities and social sciences. The collection brings together scholars from different fields within humanities and social science to engage with memorialization and damnatio memoriae across disciplines, using examples from their own research. The broad chronological and comparative scope makes the volume relevant for researchers and students of several historical periods and geographic regions.